Mixed Continuous Cultures of Polyvinyl Alcohol-Utilizing Symbionts Pseudomonas putida VM15A and Pseudomonas sp. Strain VM15C - Shimao, Masayuki (1984)
Stable mixed continuous cultures of Pseudomonas sp. strain VM15C and Pseudomonas putida VM15A, the former of which produced a polyvinyl alcohol (PVA)-degrading enzyme and the latter of which produced an essential growth factor for PVA utilization by strain VM15C, were established with PVA as the sole source of carbon and energy with chemostat cultivation. A high extent of PVA degradation was achieved at dilution rates of less than 0.030/h. The predominant strain in the cultures was the primary metabolizer of PVA, strain VM15C. The growth supporter, strain VM15A, existed as a minor population, although its population was maintained at an almost constant level throughout a dilution region in which the VM15C population decreased markedly as the dilution rate was raised. A crude growth factor which was prepared from a culture supernatant of strain VM15A and increased the specific growth rate of strain VM15C with PVA in an axenic batch culture was also effective for enhancing the VM15C population and PVA degradation in the mixed continuous culture at a high dilution rate (0.064/h). This indicated that the growth-limiting substrate for strain VM15C in the mixed continuous culture is the growth factor produced by strain VM15A.